Walking in the uncanny valley: importance of the attractiveness on the acceptance of a robot as a working partner - Destephe, Matthieu; Brandao, Martim; Kishi, Tatsuhiro; Zecca, Massimiliano; Hashimoto, Kenji; Takanishi, Atsuo (Frontiers in Psychology, 2015)
The Uncanny valley theory, which tells us that almost-human characteristics in a robot or a device could cause uneasiness in human observers, is an important research theme in the Human Robot Interaction (HRI) field. Yet, that phenomenon is still not well understood. Many have investigated the external design of humanoid robot faces and bodies but only a few studies focused on the influence of robot movements on our perception and feelings of the Uncanny valley. Moreover, no research investigated the possible relation between our uneasiness feeling and whether we would accept or not robots having a job in an office, a hospital or elsewhere. To better understand the Uncanny valley, we explore several factors which might have an influence on our perception of robots, be it related to the subjects such as culture, attitude towards robots or related to the robot such as emotions and emotional intensity displayed in its motion. We asked 69 subjects (N = 69) to rate the motions of a humanoid robot (Perceived Humanity, Eeriness and Attractiveness) and state where they would rather see the robot performing a task. Our results suggest that, among the factors we chose to test, the attitude towards robots is the main influence on the perception of the robot related to the Uncanny valley. Regarding the robot occupation acceptability, only the Attractiveness has an effect on it, mitigating any Uncanny valley effect. We discuss the implications of those findings for the Uncanny valley and the acceptability of a robotic worker in our society.